The Politics of Love in Ahmad Shamlou’s Romances - Homa Rafiei moghadam kasani; Rahman Moshtaghmehr; Naser Alizadeh Khayat (فصلنامه نقد ادبی, 2022)
Lyrical literature and hence romantic poetry is a collection of feelings, emotions and representations of human relationships which has been widely used in different eras and discourses with various even conflicting functions and manifestations. Romantic poetry, distancing from political poetry, discusses politics of literature rather than political literature. However, modern Iranian poetry, deeply connected with politics and protest literature, establishes a different relation between dramatic poetry and political poetry. Shamlou is one of the prominent poets of political poetry whose antagonism and political conflicts are sources of metaphors and constructions in romance. This paper, based on critical discourse analysis, emphasizing the concept of "antagonism" as a key concept in politics, shows that politics is related to romance in two ways. First, such romances are new experiences to represent human relationships. Second, they are against traditional literature, since Shamlou by changing the rhetoric of romantic poetry created a type of literature that is romance in surface but resistance literature in depth. Extended Abstract Iranian modern literature is fundamentally different from pre-modern literature; although the way modern literature uses the theological source of pre-modern literature is not its logical continuation. Political orders and the concepts are the most important elements of the distinction between two periods. Usually, romantic poetry is distinguished from political poetry, but Iranian modern poetry, which is connected to protest literature and political matters, has established a good relationship between romantic and political poetry. Studying he relationship between political literature and the politics of the literature is the main goal of this manuscript. The concept of “antagonism" is emphasized here as the key word in Shamlou's poetry, showing how politics is connected to romances. Firstly, these romances are new representations of human experience, and secondly it is a rhetorical change in romantic poetry, which is against the traditional literature. The most important principle that connects the concept of "articulation" to the political issues is discursive conflict; thus, for a better understanding of the conflict, political literature, and the politics of literature discourse, the concept of politics must be separated from the political orders. Any action which is beyond the realm of the individual, can influence the decisions of the society, especially the political power, and in some way modify or oppose it, and it is called a political action. Political poetry promotes the idea of anti-reading, and a political poet as an anti-reading thinks about the "enemy other". After a huge break of the Persian Constitutional Revolution, social movements and the libertarianism language took an explicit form. Literature migrated from traditional lyrical to a new space. Revealing the name of "Aida" with the poet not as a Platonic lover but as a better half living with Shamlou is a kind of conflict with the tradition of romance-writing in one hand and "Literature of resistance" from the other. In political poetry, enemy is the other, and in the romantic poem, the other is the friend. The poet of political poetry thinks about resistance; in this view, the enemy has become a focal point; because the enemy has captured a part of his unconscious like a "central metaphor". The confrontational mentality of the political poet turns the other, such as the enemy, into an object, and turns the other, such as friend and love, into a praiseworthy subject. Contemporary poetry, unlike pre-modern poetry with a negative aspect, brought the private into the domain of the public, and by highlighting the other friend in romantic poetry, created a kind of resistance and negation tool. In his poem, Shamlou clearly says that love is an epic and he sees this reversal from the eyes of the enemy. The link between love and struggle in Shamlou's poems is the internal link between the practice of personal experience and the most external political behaviors. In a general classification, historically, his life can be divided into three parts: A: The period in which the search for love gives way to experience; the experience of life and poetry, which, according to him, are "not impressions of life, but life itself". This period can be referred to as the period "before the appearance of Aida". B: The period when the poet, tired of the bitter experiences he has acquired in his personal and social life, finds another love and he moves to the house so that love becomes a refuge and a bastion where he can relieve the outside fatigue and find new strength to fight. This period starts from 1962 "Aida's appearance". C: In the third part of his life, although he still has Aida's presence, Shamlou thinks more about death and "struggle with silence" and he remembers his friends. In fact, this same love and social commitment in Shamlou's poetry makes him not distinguish between individual love and public love. From the perspective of love, three types of love can be distinguished in Shamlou's poem: 1. Romantic love without social pains.2. Personal love with social representations, and 3. General love or love of freedom and man: 1. Although romantic love is not the general indicator of the concept of love in Shamlou's poems; Shamlou has been involved with this type of love in a negative way. He considered individual and public love as opposed to romantic love, which always has the suspicion of eroticism. Romantic love can be found in Shamlou's first poetry collection, "Āhang-hāye Farāmush Shodeh (Forgotten Songs)". 2. Keeping distance from his romantic love, Shamlou discovers love in another dimension: the shadow of resistance; as it can be a strength for fighters who return to fight again. 3. By rejecting romantic love, Shamlou arrived at a special definition of man; a person who can have the courage to deny the disturbing facts and reveal himself as a fighting person. The convergence of the meanings of the two fields of politics and love has turned Samlou's poem into a different poem. From this point of view, finding the signs and codes of his romantic poetry is not compelling only in purely lyrical spaces. The enemy as a threatening other has caused Shamlou to experience new ways, because the discourse of his poetry is against the discourse of domination; whether we seek this dominance in aesthetics or in the discourse of power. It is in this situation that Shamlou glorifies the beloved as another and brings love into his poem in the atmosphere of resistance to discover a new truth. In individual romances, he uses the same signs and symbols that used before in public love. The same lover with a revolutionary face and the same revolutionary faces with the beloved cause him to not see a difference between public love and personal love.